Letters To A Young Calvinist: An Invitation To The Reformed Tradition - Yeremia Yordani Putra (Jurnal Amanat Agung, 2020)
Smith, James K. A. Letters To A Young Calvinist:  An Invitation To The Reformed Tradition (Grand rapids: Brazos, 2010), 134 halaman